2009
DOI: 10.1021/nl901232p
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Crystal Geometry for Organic Solar Cells

Abstract: We report organic solar cells with a photonic crystal nanostructure embossed in the photoactive bulk heterojunction layer, a topography that exhibits a 3-fold enhancement of the absorption in specific regions of the solar spectrum in part through multiple excitation resonances. The photonic crystal geometry is fabricated using a materials-agnostic process called PRINT wherein highly ordered arrays of nanoscale features are readily made in a single processing step over wide areas (∼4 cm 2 ) that is scalable. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
191
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(194 citation statements)
references
References 33 publications
2
191
0
1
Order By: Relevance
“…Photonic crystal slabs are used in many applications including surface-emitting lasers [23], photovoltaics [24], LEDs [25], and biosensing [26][27][28]. The periodic modulation alters the dispersion relation of light in the slabs and gives rise to photonic bands, analogous to electronic band structures in solids.…”
mentioning
confidence: 99%
“…Photonic crystal slabs are used in many applications including surface-emitting lasers [23], photovoltaics [24], LEDs [25], and biosensing [26][27][28]. The periodic modulation alters the dispersion relation of light in the slabs and gives rise to photonic bands, analogous to electronic band structures in solids.…”
mentioning
confidence: 99%
“…We propose the growth of fluorescent composite photonic crystals from blends of "solvent-compatible" noncovalently bonded nanosphere-polymer systems as a general method for achieving a uniform distribution of polymeric dopants in three-dimensional self-assembling photonic structures. Photonic crystals (PhCs) 1, 2 have been widely investigated over the last two decades and are now proposed in applications such as light-emitting diodes (LEDs), 3 solar cells, 4,5 and lasers. 6,7 Among them, self-assembled PhCs have been studied in detail due to their low cost of fabrication and ease of preparation, with artificial opals 1,2,8,9 being especially popular.…”
mentioning
confidence: 99%
“…More specifically, for applications to photovoltaics it has been shown that trapping light beyond the commonly accepted limit of Lambertian light scattering is possible through the use of periodic photonic nanostructures [7][8]. The optical properties of such structures have been widely studied theoretically [9][10][11][12][13] and their integration has been mainly tried in a-Si, micromorph and organic based cells [14][15][16].…”
mentioning
confidence: 99%